Islam sebagai Agama dan Umat: Analisa Pemikiran Kenegaraan Jamâl al-Bannâ - Mukhammad Zamzami (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2011)
This article explores Jamâl al-Bannâ’s view on the relation between religion and state, particularly his views on the relation system between Islam and state, and the related issues such as democracy, pluralism, and secularism. Therefore, the article describes issues on the concept of ummah in Islam, democracy within the Islamic governmental system, and Islam’s view on secularism and pluralism. The article uses a textual interpretation method. The article finds that the ideal example of an Islamic government was the period of Madînah al-Munawwarah, which only lasted for 25 years.